Peace with God - Graham, Billy (Waco, Tex. Word Books, 1984)
"Peace With God points the way, the only way, to authentic personal peace in a world in crisis."--Billy Graham.
Keywords: Theology, Doctrinal -- Popular works. Christian life -- Baptist authors. Theology, Doctrinal